2012
DOI: 10.1029/2011gl050086
|View full text |Cite
|
Sign up to set email alerts
|

The role of the ocean in the global atmospheric budget of acetone

Abstract: [1] Acetone is one of the most abundant carbonyl compounds in the atmosphere and it plays an important role in atmospheric chemistry. The role of the ocean in the global atmospheric acetone budget is highly uncertain, with past studies reaching opposite conclusions as to whether the ocean is a source or sink. Here we use a global 3-D chemical transport model (GEOS-Chem) simulation of atmospheric acetone to evaluate the role of air-sea exchange in the global budget. Inclusion of updated (slower) photolysis loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
214
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 124 publications
(238 citation statements)
references
References 71 publications
22
214
2
Order By: Relevance
“…Specifically, Blitz et al (2004) measured the quantum yields to be substantially lower than previously reported. Those findings imply an increased acetone lifetime, and reverse the relative importance of photolysis and OH oxidation as acetone sinks (Fischer et al, 2012). They also modify the importance of acetone as a precursor of HO x and PAN (Arnold et al, 2005), leading to less PAN in the Northern Hemisphere (especially in the upper troposphere), but more PAN in parts of the Southern Hemisphere.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Specifically, Blitz et al (2004) measured the quantum yields to be substantially lower than previously reported. Those findings imply an increased acetone lifetime, and reverse the relative importance of photolysis and OH oxidation as acetone sinks (Fischer et al, 2012). They also modify the importance of acetone as a precursor of HO x and PAN (Arnold et al, 2005), leading to less PAN in the Northern Hemisphere (especially in the upper troposphere), but more PAN in parts of the Southern Hemisphere.…”
Section: Introductionmentioning
confidence: 96%
“…Other terrestrial sources include biomass burning (Simpson et al, 2011) and direct anthropogenic emissions (Goldan et al, 1995;Goldstein and Schade, 2000;de Gouw et al, 2005). Globally, the oceans appear to be both a gross source and a gross sink for atmospheric acetone (Fischer et al, 2012); however, the magnitude and variability of the corresponding net flux is quite uncertain (de Reus et al, 2003;Williams et al, 2004;Lewis et al, 2005;Marandino et al, 2005;Sinha et al, 2007;Taddei et al, 2009;Fischer et al, 2012;Read et al, 2012;Sjostedt et al, 2012). Along with gross oceanic uptake, sinks of atmospheric acetone include photochemical oxidation by OH, photolysis, and deposition to land (Chatfield et al, 1987;McKeen et al, 1997;Gierczak et al, 1998;Blitz et al, 2004;Karl et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Photolysis rates use the FAST-JX scheme (Bian and Prather, 2002;Mao et al, 2010), with acetone photolysis rates updated by Fischer et al (2012). Stratospheric chemistry is based on LINOZ McLinden et al (2000) for O 3 and a linearised mechanism for other species as described by Murray et al (2012).…”
Section: Global Modelmentioning
confidence: 99%